2000
DOI: 10.1053/eujp.2000.0186
|View full text |Cite
|
Sign up to set email alerts
|

The development and validation of a Greek version of the short‐form McGill Pain Questionnaire

Abstract: A Greek version of the SFMPQ (the GR-SFMPQ) has been constructed which has the properties of internal validity and consistency. It is easy to administer, easy to understand even for an elementary educational level and it is capable of describing multidimensionally the pain experience of chronic musculoskeletal pain patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 11 publications
8
46
0
3
Order By: Relevance
“…From the 53 eligible studies, 44 different versions of the MPQ were identified (there is more than one study reporting the clinimetric testing of the Spanish [14], Japanese [21], Dutch [22], Czech [23], Greek [24], and Norwegian [25] versions). The 44 versions represent 26 different language/ cultures as there are multiple versions for the same language (4 Dutch, 4 German (being one in German-Berne [15]), 4 Norwegian, 3 Greek, 2 Brazilian-Portuguese, 2 Danish, 2 Italian, 2 Chinese, 2 Korean, 2 Turkish, 2 Japanese, and 2 Spanish versions (being one developed for Mexican-Americans [26] and another developed in Spain [14] and tested in Argentina, Costa Rica, Mexico, Panama, and Spain [27]).…”
Section: Resultsmentioning
confidence: 99%
“…From the 53 eligible studies, 44 different versions of the MPQ were identified (there is more than one study reporting the clinimetric testing of the Spanish [14], Japanese [21], Dutch [22], Czech [23], Greek [24], and Norwegian [25] versions). The 44 versions represent 26 different language/ cultures as there are multiple versions for the same language (4 Dutch, 4 German (being one in German-Berne [15]), 4 Norwegian, 3 Greek, 2 Brazilian-Portuguese, 2 Danish, 2 Italian, 2 Chinese, 2 Korean, 2 Turkish, 2 Japanese, and 2 Spanish versions (being one developed for Mexican-Americans [26] and another developed in Spain [14] and tested in Argentina, Costa Rica, Mexico, Panama, and Spain [27]).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Melzack himself developed the ShortForm McGill Pain Questionnaire (SF-MPQ) (18), which just takes 2Á5 min to administer, and gives information about the basic attributes of pain quality and pain intensity. So far, the instrument has been translated as well as validated into five languages: Czech (19), Swedish (20), Greek (21), Korean (22) and Thai (23). It has also been transformed to several languages by simple translation of the descriptors and other words (Mapi Research Institute; 24).…”
Section: Introductionmentioning
confidence: 99%
“…The validity and reliability of the English version were examined using a large sample, similar to or larger than other studies in which other measures were translated and validated [51][52][53][54][55]. Unidimensionality was confirmed and reliability was acceptable for both versions.…”
Section: Clinical Relevancementioning
confidence: 99%